Classification of Igbo musical instruments, Nigeria - Lo-Bamijoko, Joy N. (International Library of African Music, 1987)
The major task of this study is to place indigenous instruments in an indigenous framework. The lists of musical instruments presented here do not pretend to cover the wide variations of all Nigerian musical instruments. Rather, the purpose of the survey is to give a broad overview of Igbo musical instruments, as well as to show how musical instruments of some of the other cultures of Nigeria relate to those of the Igbos, and how they relate to the classification of musical instruments as a whole. In Nigeria, and specifically among the Igbo-speaking people, the classification of musical instruments takes two factors into consideration. The first focuses on the instrument per se, the second on the society in which the instrument is used. The first factor, in other words, deals with the classification of the instruments based upon how they are played, and the second with the various functions of the instruments in the indigenous context.
Keywords: Musical instruments; Igbo (African people); African Music; Nigeria